Islamic-Javanese Syncretism in the Sunan Kalijaga Dance by Wahyu Santosa Prabowo - Janggan Mustika Jati; Wasi Bantolo (Jurnal Seni Tari, 2025)
This research aims to analyze Islamic-Javanese syncretism reflected in Sunan Kalijaga's dance works. Sunan Kalijaga, as one of the Wali Sanga, played an important role in the spread of Islam in Java by integrating elements of local culture into religious practices. This study uses a qualitative approach with textual analysis and observation methods of dance performances inspired by the teachings of Sunan Kalijaga. The results of the study show that the dance presented is not only a form of artistic expression, but also combines Islamic values with Javanese traditions. The symbolic elements in the movements, costumes, and music reflect the blend of Islamic teachings and local culture. This research also identifies the social and cultural impact of this syncretism on the Javanese community, as well as how dance becomes a medium to strengthen religious and cultural identity.